THE COMMONWEALTH OF INDEPENDENT STATES ON THE MILLENNIUM CHALLENGE ACCOUNT SELECTION INDICATORS: OVERNANCE IS THE MAIN CHALLENGE - KOBONBAEV, Maks (CENTRAL ASIA AND THE CAUCASUS, 2006)
On March 2002, in Monterrey, Mexico, President Bush announced the creation of a bilateral development fund, the MCA, as the U.S. contribution to the United Nations Conference on Financing for Development. According to the plan, Bush pledged US1.7 billion for FY 2004, US3.3 billion for FY 2005 and US5 billion for FY 2006, representing a 50 percent increase in the amount of aid focused strictly on development assistance.1 This marshaled the largest U.S. foreign aid increase in decades. Steve Radelet wrote in Foreign Affairs, “This move was one of the greatest surprises of George W. Bush’s presidency so far.”2 Indeed, the MCA could bring about the most fundamental changes to U.S. foreign assistance policy since the Kennedy administration.3 Historically, the bulk of U.S. foreign assistance did not have economic development as its pri-mary purpose. Instead, it was based on foreign policy goals. Brainard et al. note that though development assistance was originally intended to address development needs, decisions on aid allocation were based on foreign policy priorities.4 In other words, aid was given primarily to strategic partners though it depended on recipient countries whether they used aid for their growth. During the Cold War, foreign aid was mainly allocated to contain communism. For example, Taiwan, South Korea, Turkey, Vietnam, and others have received aid from the U.S. on this principle. In addition to the containment of communism, the aid was allocated to advance U.S. foreign policy in hydrocarbon abundant Middle East. As a part of the Camp David accords, Washington also provided a large share of ESF5 to Egypt and Israel, which are considered the largest aid recipients up to this day.6 The allocation of aid on strategic considerations has continued to be the dominant modus oper-andi long after the end of the Cold War. For example, after the demise of the U.S.S.R, the U.S. has been very active in providing assistance to the formerly communist countries to advance democratic and free-market reforms. The political gains have been tangible as well. Eastern Europe and Baltic States have joined the European Union and popular democratic revolutions have occurred in Georgia, Ukraine and Kyrgyzstan. However, outside of formerly communist countries, Middle East and Southeast Asia, the U.S. has somewhat lost coherent strategic rationale for aid allocation. The overall U.S. assistance to poor countries also fell by 25 percent.7